Study on the Relationship Between the Interface Design and the User’s Consumption Level of TikTok App - Cheah, Kim Mun; Soon, Eu Hui; Feng, Hengzhong (INTI International University, 2024)
The habits of media consumers have undergone a profound shift, with short video content becoming a dominant trend, particularly among millennials and Generation Z. TikTok, as a leader in this space, has gained global popularity, yet limited research exists about its consumption patterns in Malaysia. This study investigates the relationship between TikTok’s interface design and user consumption levels among Malaysian centennial users (ages 18-24). Using a quantitative survey of 40 respondents, the findings reveal a high level of TikTok consumption in terms of time spent and engagement. Statistical analysis via SPSS confirms that TikTok’s interface design significantly influences user consumption behavior. These findings highlight the critical role of interface design in shaping the consumption dynamics of short-video apps, and ideally align to supporting Sustainable Development Goals 12 (SDG 12).